Declaração Universal dos Direitos Humanos: autoridade, significado e natureza jurídica - Fredys Orlando Sorto (Araucaria)
The idea that only the State is subject to International Law lingered for many years. At present it is undeniable the existence of other subjects, among which, the human being. This article deals with the movement which acclaims the human being as subject to rights and analyses the main declarative instrument of these rights in the international society: The Universal Declaration of Human Rights (1948). It is an incomparable document in the History of Mankind, for it is a revolutionary document that causes profound changes of mentality and attitude in the world.